2021
DOI: 10.1111/1467-8578.12359
|View full text |Cite
|
Sign up to set email alerts
|

Uncharted territory and extraordinary times: the SENCo's experiences of leading special education during a pandemic in England

Abstract: This research focuses on the impact of the context of Covid-19 on the role of the SENCo in English schools. The SENCo's role is a contested field; however, the current Special Educational Needs Code of Practice identifies 11 key areas of SENCos' work. A widely distributed survey was used to access the voice of SENCos across the country, and received 26 responses. Data were analysed using a realistic evaluation framework to identify the impact of Covid-19 on the work of the SENCo. The research indicated that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…During the peak of the pandemic the survey findings suggested that SENCos were required to undertaking additional teaching or SLT duties, in response to needs in school at that time. This echoes the findings from Middleton and Kay which suggested that SENCOs may have ‘steeped into the breach to fulfil roles needed within the school owing to contextual challenges’ (2021, p. 220). Although it not a new phenomenon.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…During the peak of the pandemic the survey findings suggested that SENCos were required to undertaking additional teaching or SLT duties, in response to needs in school at that time. This echoes the findings from Middleton and Kay which suggested that SENCOs may have ‘steeped into the breach to fulfil roles needed within the school owing to contextual challenges’ (2021, p. 220). Although it not a new phenomenon.…”
Section: Discussionsupporting
confidence: 70%
“…An immediate change which took place at the start of the pandemic was the move to remote and online methods of communication (Middleton and Kay, 2021). The survey findings suggest that this change helped with the aforementioned increase in contact with families.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the challenges faced by SEND professionals in the circumstances of the pandemic in England. For example, Middleton and Kay (2021) surveyed a small group of SENCOs on the impact of COVID-19 on the work that they do. The study concluded that SENCOs' responsibilities have widened to include more administrative tasks, more emotional support to staff and students and also the need for a closer partnership with senior leaders and governors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have referred to the challenges of adapting to online teaching, the lack of preparedness of staff and the need to think about the future for faster adaptiveness to changes in teaching methods (Greenway and Eaton-Thomas, 2020;Steed et al, 2021). However, scarce evidence is available on how these settings have dealt with the challenges posed by COVID-19, with extant studies being small-scale in nature (e.g., Crane et al, 2021;Lukkari, 2021;Middleton and Kay, 2021;Sayman and Cornell, 2021). This seems particularly important in England, where the number of children with SEND attending specialised settings as well as the number of special schools has been rising year on year since 2017 (Department for Education, 2021).…”
mentioning
confidence: 99%
“…Several studies point to a divergence between policy intent and the realities of the SENCo role in day-to-day practice; Lin et al (2021a) argue that membership of the SLT did not seem to be a crucial factor impacting on SENCo identity; similarly, Poon-McBrayer (2012) found that SENCos in Hong Kong fulfil management roles but are not successful at leading their schools in shaping special educational needs provision. This pattern has continued during the pandemic with Middleton and Kay (2021) and Clarke and Done (2021) expressing concerns around the degree to which SENCos have been able to inhabit leadership roles.…”
Section: Challengementioning
confidence: 99%